Color, vitamin C, β-carotene and sensory quality retention in microwave-assisted thermally sterilized sweet potato puree: Effects of polymeric package gas barrier during storage. (September 2019) - Zhang, Hongchao; Patel, Juhi; Bhunia, Kanishka; Al-Ghamdi, Saleh; Sonar, Chandrashekhar R.; Ross, Carolyn F.; Tang, Juming; Sablani, Shyam S.
Graphical abstract: Highlights: Packaging significantly ( p < 0.001) affected L*, ΔE and vitamin C during storage. MATS reduced VC/β-carotene content from 201 ± 4.7/68 ± 3.0 to 186 ± 15.6/72 ± 6.2 mg/100 g. Pouches with OTR < 0.3 cc/m 2 ⋅day have similar color/vitamin C retention as foil pouch. More than 77% of consumers accepted MATS processed puree throughout 18 months. Abstract: In this study, we investigated the effects of package barrier properties on shelf-life of vitamin C-fortified sweet potato puree (SPP) processed with microwave-assisted thermal sterilization (MATS). Results show a change in SPP color during both processing and storage. The vitamin C in SPP decreased from 201.7 ± 4.7 to 185.8 ± 15.6 mg/100g during MATS and further decreased to as low as 13.6 ± 4.1 and 10.0 ± 0.3 mg/100g the end of 9 or 18 month, depending on the oxygen barrier and temperature. The total β-carotene content after processing and storage was slightly higher than before processing. Pouches with oxygen transmission rates (OTRs) of less than 0.3 cc/m 2 ⋅day showed higher retention of color, vitamin C, and predicted shelf life than other pouches. However, this did not affect the consumer acceptance. Most panelists considered MATS processed SPP as a desirable baby food throughout the 18 months. Efforts are still needed to stabilize vitamin C content for over 3 years for military and NASA missions.